Extracellular vesicles in age-related diseases: disease pathogenesis, intervention, and biomarker - Puan Haliza Lintang Putri; Samira Husen Alamudi; Xuan Dong; Ying Fu (Stem Cell Research & Therapy)
Abstract Aging is a multifactorial biological process characterized by the irreversible accumulation of molecular damage, leading to an increased risk of age-related diseases. With the global prominent rise in aging populations, elucidating the mechanisms underlying the aging process and developing strategies to combat age-related diseases have become a pressing priority. Extracellular vesicles (EVs) have gained significant attention due to their role in intercellular communication. EVs are known for their ability to deliver biocargoes, such as miRNA, proteins, and lipids, implicating their involvement in disease pathogenesis and intervention. In this review article, we explore the dual role of EVs in age-related diseases: contributing to the pathogenesis of diseases by transferring deleterious molecules, while also offering therapeutic ability by transferring beneficial molecules. We also highlight the application of EVs as biomarkers for early diagnosis of age-related diseases, paving the way for early intervention and precision medicine. Additionally, we discuss how analysing the composition of EVs cargo can provide insights into disease progression. Finally, we address the challenges and future perspectives of EV-based-therapy in clinical translation, including standardization of EVs isolation methods and improving cargo specificity. Graphical abstract